Ciencia y Humanidades. El umbral de las dos culturas. - Fernández, Javier (My University, 2019)
In the development of the cognitive reason, philosophy and science were always related. However, as knowledge progressed, field differentiation became more and more necessary; but in our time that strict parceling must be left behind. Today, a new critical reflection is required to be remounted above the division separating knowledge according to the dichotomy of Nature Sciences, on the one hand; and Human or Spirit Sciences, on the other. This schematism is the reflection of an illusory understanding of nature as if it were an area of reality alien to man, and as if human beings were a “subject” disconnected from the natural order. Such a classification reflects a rupture between nature and society, which blocks the possibilities of a comprehensive understanding of reality. 21st century humanism must overcome such a dichotomy, since science has become an essential activity for humanity to be present in multiple spheres of culture, from health services to food production, communications, recreation, politics, economics, education, et
En el desarrollo de la razón cognoscitiva, filosofía y ciencia estuvieron siempre relacionadas. Sin embargo, a medida que el conocimiento fue progresando, la diferenciación de campos se hizo cada vez más necesaria; no obstante, en nuestro tiempo esa parcelación estricta debe quedar atrás. Hoy se requiere de una nueva reflexión crítica que se remonte por encima de la división que separa el conocimiento según la dicotomía de Ciencias de la naturaleza, por una parte, y Ciencias humanas o del espíritu, por otra. Este esquematismo es el reflejo de una ilusoria comprensión de la naturaleza como si ésta constituyera un ámbito de realidad ajeno al hombre, y como si el ser humano fuese un “sujeto” desvinculado del orden natural. Tal clasificación refleja una ruptura entre naturaleza y sociedad, que bloquea las posibilidades de una comprensión integral de la realidad. El humanismo del siglo XXI debe superar tal dicotomía, ya que la ciencia se ha hecho una actividad esencial para la humanidad al estar presente en múltiples esferas de la cultura, desde los servicios de salud hasta la producción de alimentos, las comunicaciones, la recreación, la política, la economía, la educación, etcétera.
Keywords: EXPLICACIÓN; COMPRENSIÓN; HERMENÉUTICA; RACIONALIDAD